Phenolic, Flavonoid, and Antioxidant Profiles of Sago (Metroxylon sagu Rottb.) Leaf Ethanol Extract - Muhammad Isrul; Bai Athur Ridwan; Ahmad Syaiful; Azlimin Azlimin; Tenri Zulfa Ayu Dwi Putri; Eviyanti Jambilu; Mahfuzun Bone; Vina Maulidya (Institute for Research and Community Services Universitas Muhammadiyah Palangkaraya, 2025)
Oxidative stress drives many degenerative conditions, motivating the search for safe, plant-based antioxidants. Sago (Metroxylon sagu Rottb.) leaf is comparatively underexplored. This study evaluated its antioxidant activity and related it to phenolic and flavonoid contents. A 96% ethanolic leaf extract was assayed for radical-scavenging activity by DPPH using ascorbic acid as the positive control; IC50 values were obtained from linear regression of % inhibition versus concentration (2.5–10 ppm). Composition was profiled by total phenolic content (TPC; Folin–Ciocalteu, expressed as mg gallic acid equivalents per g, mg GAE/g) and total flavonoid content (TFC; AlCl3 colorimetry, expressed as mg quercetin equivalents per g, mg QE/g). The extract showed very strong DPPH activity (IC50 = 11.873 ± 0.025 µg/mL), while ascorbic acid yielded 3.166 ± 0.025 µg/mL; both fall within the <50 µg/mL category. The extract contained TPC = 1.61% w/w ( 16.1 mg GAE/g) and TFC = 3.05% w/w (reported on the quercetin-equivalent scale). These indices are consistent with the low IC50 and support a phenolic-driven antioxidant profile. Metroxylon sagu leaf extract exhibits very strong radical-scavenging activity, supported by appreciable levels of phenolics and flavonoids, which identify M. sagu leaves as a promising natural antioxidant source. The findings provide a concise quantitative basis for follow-up work focused on targeted phenolic/flavonoid profiling, as well as broader antioxidant evaluations.